(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Antibiotics changed everything. For the first time in human history, a simple bacterial infection was no longer a death sentence. Pneumonia, sepsis, tuberculosis — diseases that had killed without mercy for centuries — became treatable within days. Then bacteria did what they have always done throughout billions of years of evolution. They adapted! Antibiotic resistance has quietly become one of the defining medical crises of this century.